2011
DOI: 10.1117/12.913960
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric, two-color, photon-counting laser altimeter measurements of forest canopy structure

Abstract: Laser altimeter measurements of forest stands with distinct structures and compositions have been acquired at 532 nm (green) and 1064 nm (near-infrared) wavelengths and parallel and perpendicular polarization states using the Slope Imaging Multi-polarization Photon Counting Lidar (SIMPL). The micropulse, single photon ranging measurement approach employed by SIMPL provides canopy structure measurements with high vertical and spatial resolution. Using a height distribution analysis method adapted from conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…They concluded that the atmospheric conditions have an impact on the range measurement. The suitability of the wavelength for vegetation measurements has also been discussed, but Harding et al [15] stated that there are small differences between 532 nm systems and 1064 nm single photon systems when it comes to height of median energy and canopy cover metrics. Most of the studies with SPL data so far have looked at the possibility to generate a DEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the atmospheric conditions have an impact on the range measurement. The suitability of the wavelength for vegetation measurements has also been discussed, but Harding et al [15] stated that there are small differences between 532 nm systems and 1064 nm single photon systems when it comes to height of median energy and canopy cover metrics. Most of the studies with SPL data so far have looked at the possibility to generate a DEM.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have evaluated the SPL data for analyzes of vegetation characteristics. Harding et al concluded that the SPL delivers data with structural measurements of high resolution and that estimations of forest variables could be made from similar metrics and with similar accuracy as conventional systems [15]. Swatantran et al [16] compared height percentiles from SPL and linear lidar systems with field-measured tree heights.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-photon lidar systems utilize high energy laser beams with long pulse widths 3 20 to capture energy scattered from the target (ground surface or canopy). Single photon lidar systems in contrast, transmit a shorter and lower energy pulse and detect scattered energy more efficiently ( Fig.…”
mentioning
confidence: 99%
“…Recent research, mostly in support of the ICESat-2 21 mission has shown that canopy height and ground elevation can be determined with moderate accuracy from low density photon counting data after noise filtering 16 20 22 23 24 . Scheduled for deployment in 2017, ICESat-2 utilizes a SPL instrument called ATLAS (Advanced Topographic Laser Altimeter System).…”
mentioning
confidence: 99%
“…Recent developments in lidar technology have generated new full waveform scanners that can record more efficiently the backscatter pulses within the travel path of a laser beam to provide additional information about the characteristics of reflected objects and a higher spatial point density (Reitberger et al, 2009;Yao and Stilla, 2010;Wallace et al, 2012;Gong et al, 2015;Scaioni et al, 2018). Furthermore, in certain practical applications Single-Photon lidar (532 nm green laser) and Geiger-mode lidar (1064 nm IR laser) have recently gained popularity (Swatantran et al, 2016;Stoker et al, 2016;Harding et al, 2011). Both Geiger and Single-Photon lidar systems utilize focal plane array detectors and record the returned laser pulse using an array of receivers instead of a single receiver.…”
Section: Lidar Remote Sensing Of Forest Structurementioning
confidence: 99%